Studi Pengolahan Sagu (Metroxylon sp.) Oleh Masyarakat Kampung Malawor Distrik Makbon Kabupaten Sorong - Irnawati, Irnawati; Kahar, Muhammad Syahrul; Budiarti, Marlinda Indah Eka (Universitas Muhammadiyah Surabaya, 2018)
Sago tree (Metroxilon sp.) Is native to Southeast Asia. The method used in this research is to use descriptive method with case study and free interview (free interview) field in processing sago and sago tree species which in though. Village community Malawor District Makbon Sorong regency has long consumed sago from natural forests and some sago already planted by ancestors hereditary. When rice and yams run out, people consume sago as a substitute. Most people still manage sago using traditional method for that which become problem point of this research is how kind of sago, process of traditional and semi traditional (scar machine) along with economical value of processed sago which can by community of Kampung Malawor District of Makbon Regency SorongÂ